One Health Integration: A Proposed Framework for a Study on Veterinarians and Zoonotic Disease Management in Ghana - Valeix, Sophie Françoise (Frontiers in Veterinary Science, 2018)
In parallel with the recent world-wide promotion of One Health (OH) as a policy concept, a growing body of social science studies has raised questions about how successful OH policies and programs have been in managing some global health issues, such as zoonotic diseases. This paper briefly reviews this literature to clarify its critical perspective. Much of the literature on OH also is focused on health management at an international level and has paid less attention to implementation programs and policies for OH at the national and local levels, especially in low-and-middle-income countries (LMICs). Programs to implement OH often are linked to the concept of “integration”, a notion that lacks a universal definition, but is nonetheless a central tenet and goal in many OH programs. At the local and national levels, strong differences in perspectives about OH among different professions can be major barriers to integration of those professions into OH implementation. Policies based on integration among professions in sectors like animal, human and environmental health can threaten professions’ identities and thus may meet with resistance. Taking into account these criticisms of OH research and implementation, this paper proposes a research framework to probe the dominant social dimensions and power dynamics among professional participants that affect OH implementation programs at the local and national levels in a low-income country. The proposed research focus is the veterinary profession and one aspect of OH in which veterinarians are necessary actors: zoonotic disease management. Results from research framed in this way can have immediate application to the programs under study and can inform more expansive research on the social determinants of successful implementation of OH programs and policies.